Demand for milk and milk products in the rural household of Bangladesh: A panel data analysis - Eshrat Jahan Mahfuza; Mohammad Jahangir Alam; Andrew M. McKenzie (Journal of Agriculture and Food Research)
Milk is considered an essential source of protein for people of all ages. However, Bangladeshi people, particularly those living in rural areas, tend to consume less milk and milk products than necessary. Therefore, this study aims to investigate the demand for milk and milk products among rural consumers and the factors affecting their consumption habits. The study utilizes balanced panel data from three waves of the Bangladesh Integrated Household Survey: 2011–12, 2015, and 2018–19, collected by the International Food Policy Research Institute. Both the Almost Ideal Demand System (AIDS) and Fixed Effects Model were employed. The expenditure elasticity for liquid milk, powdered milk, and condensed milk was found to be 1.013, 1.856, and 1.060, respectively, indicating that these products are considered luxury goods in rural Bangladesh. Additionally, powdered milk is more price-sensitive than liquid or condensed milk in these areas. Milk and milk products exhibit a substitutable relationship based on the Slutsky and Cournot cross-price elasticities matrix. Consumption of liquid milk is significantly influenced, either positively or negatively, by several factors, including age, education, family size, ownership of dairy animals, income, expense of food, and year. Furthermore, while the consumption of powdered milk is increasing over time, factors such as family size and livestock ownership negatively impact its consumption. Similarly, the consumption of condensed milk is negatively affected by education and ownership of dairy animals. Based on our study results, we recommend increasing household income through on and off-farm job creation, promoting educational campaigns on the benefits of milk, and supporting livestock ownership to reduce reliance on processed milk products.